Powody uniwersalnej i trwałej współpracy - Klimczak, Bożena (Reasons of the universal and durable cooperation, 2005)
The subject of this paper are the reasons of - and for the cooperation. Several points of view in this subject are discussed, namely, selfishness rational outcome-oriented, selfishness relational process-oriented and nonselfishness. The main problem is: what are the reasons of the universal and durable cooperation? The answer is, that motivation to collective action is a mixed one, but the universal and durable cooperation requires nonselfish orientation, some people and the process-oriented selfish majority.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 42-55